B = x²+6x-4+2y-(5x-x²+3y-4)+2xy
B = x²+6x-4+2y-(5x-x²+3y-4)+2xy
= -1²+6*(-1)-4+2*3-(5*(-1)-(-1)²+3*3-4)+2*(-1)*3
= 1-6-4+5-(-5-1+9-4)-5
= 1-6-4+5+5+1-9+4-5
=-8

Réponses

2014-03-18T13:56:52+01:00
Ex: résultat sus forme la plus simple possible désoler mes très important
A: 3/7x(7/3-5/6)
B:3/7x7/3-5/6
C:12x(1/3-1/6)
D:12x1/3-1/6
ex2:calcul d'une expression 
a.                  B.                   A+b.            A-b.          Axb
11/9.           7/9.                  ..?..              ..?..             ..?..
3/4.              3/16.               ..?..             ..?..             ..?..
Meilleure réponse !
2014-03-18T14:14:50+01:00
1)
B =x²+6x-4+2y-(5x-x²+3y-4)+2xy
B = x²+6x-4+2y-5x+x²-3y+4+2xy
B= 2x²+x-y+2xy

2) x=-1 et y= 3
B=2(-1)²+(-1)-3+2*3*(-1)
B=2-1-3-6=2-10=-8
B=-8